PERANCANGAN SISTEM INFORMASI PENDATAAN PROGRAM BERSERI, ADIWIYATA, ECO-PESANTREN, DAN PROKLIM BERBASIS WEB - Ayu Dia Wulandari; Irma Yunita; Bani Wimala Prahardini (CV. Denasya Smart Publisher, 2025)
This study developed a web-based information system for the BERSERI, Adiwiyata, Eco-Pesantren, and ProKlim programs at the Banyuwangi Environmental Agency (DLH). Currently, the data collection process has been done manually, resulting in data duplication, delays in reporting, and difficulties in information integration. The method applied is the Waterfall model of the System Development Life Cycle (SDLC) with data collection through observation, interviews, and literature studies. The result of this study is a system design using PHP and MySQL with features for data input, searching, generating automatic reports, and providing integrated storage. This system is expected to improve efficiency, accuracy, and support the digitalization of public services in the environmental sector.